Dementia in Parkinson's Disease Correlates with α-Synuclein Pathology but Not with Cortical Astrogliosis - Simone A. van den Berge; Josta T. Kevenaar; Jacqueline A. Sluijs; Elly M. Hol (Parkinson's Disease)
Dementia is a common feature in Parkinson’s disease (PD) and is considered to be the result of limbic and cortical Lewy bodies and/or Alzheimer changes. Astrogliosis may also affect the development of dementia, since it correlates well with declining cognition in Alzheimer patients. Thus, we determined whether cortical astrogliosis occurs in PD, whether it is related to dementia, and whether this is reflected by the presence of glial fibrillary acidic protein (GFAP) and vimentin in cerebrospinal fluid (CSF). We have examined these proteins by immunohistochemistry in the frontal cortex and by Western blot in CSF of cases with PD, PD with dementia (PDD), dementia with Lewy bodies (DLB) and nondemented controls. We were neither able to detect an increase in cortical astrogliosis in PD, PDD, or DLB nor could we observe a correlation between the extent of astrogliosis and the degree of dementia. The levels of GFAP and vimentin in CSF did not correlate to the extent of astrogliosis or dementia. We did confirm the previously identified positive correlation between the presence of cortical Lewy bodies and dementia in PD. In conclusion, we have shown that cortical astrogliosis is not associated with the cognitive decline in Lewy body-related dementia.